Information and communication environment as a resource and tool for foreign language education of specialists - Kovaleva, Татьяна Григорьевна; Dement'eva, Татьяна Георгиевна (Journal of Civil Protection, 2022)
Purpose. To highlight the resource and methodological aspects of modern information and communication technologies for foreign language education of specialists. To reveal the prospects and problems of teaching foreign language communication in modern conditions of the dominant Internet while maintaining traditional approaches to teaching a foreign language. Methods. Critical analysis of theoretical sources on the implementation of information and communication technologies in the pedagogical process. Generalization of the practical experience of foreign language education of workers in the field of life safety and students of the University of Civil Protection. Findings. The resource and methodological advantages of modern information and communication systems and technologies used to form and develop the foreign language communicative competence of specialists, in particular the technology of distance teaching in the elements of English communication of rescue service workers, are revealed. The recommendations are given on the most effective methodological use of modern tools and resources necessary for the linguistic education of specialists in the field of life safety. Application field of research. Information and communication support of the pedagogical process of teaching communication, including foreign language. Methodology and practice of teaching intercultural communication, taking into account the modern level of information technology.